(untitled) (Sains Humanika, 2015)
Takaful industry in Malaysia has reached about 30 years. Various changes have been made by regulators of Bank Negara Malaysia (BNM) to ensure the strengthening and stability of the takaful industry including Shariah governance-related legislation. Therefore, this paper will describe the implications Takaful Act 1984, Central Bank of Malaysia Act 2009 and Islamic Financial Services Act 2013 in the shariah governance aspect of takaful industry in Malaysia. This paper also reviewing the case Teng Gia Hwa & 1 or v Syarikat Takaful Malaysia Bhd 2010 based on the latest legislative syariah governance takaful industry in Malaysia.